Evaluación de la situación actual de los emprendimientos y su desempeño en la ciudad de Loja - Ortega Jaramillo, Juan Carlos (2022)
The following degree work deals with the study and analysis of the current situation of the entrepreneurships and their performance in the city of Loja, based on what happened during the period of pandemic and confinement, direct cause of the proliferation of the SARS-CoV-2 virus, which led to complications in the exercise of the activities of entrepreneurs, influencing the decisions that led to different paths to their businesses. For this purpose, a survey format was designed and applied to a target number of 150 entrepreneurships, which then contributed to obtain the necessary information for the process of defining the characteristics and variables leading to the development of the work. Consequently, the results evidenced the state of the different entrepreneurships, as well as the action in response to the situation by the entrepreneurs, which allowed outlining a series of proposals that with the help of the use of platforms located on the internet and in a digital way, gave way to the application of online stores as other updated services which will facilitate the person who is dedicated to this type of activity to obtain a better performance of their actions and thus direct the Lojano entrepreneurship to a satisfactory economic reactivation. Likewise, conclusions are presented which show that the results proposed in the research will encourage these businesses to become more familiar with the application of new resources and in turn allow them to obtain an optimal management of their work in the environment.